Identification and characterization of genes frequently responsive to Xanthomonas oryzae pv. oryzae and Magnaporthe oryzae infections in rice - Kong, Weiwen (BMC Genomics, 2020)
BACKGROUND: Disease resistance is an important factor that impacts rice production. However, the mechanisms underlying rice disease resistance remain to be elucidated. RESULTS: Here, we show that a robust set of genes has been defined in rice response to the infections of Xanthomonas oryzae pv. oryzae (Xoo) and Magnaporthe oryzae (Mor). We conducted a comprehensive analysis of the available microarray data from a variety of rice samples with inoculation of Xoo and Mor. A set of 12,932 genes was identified to be regulated by Xoo and another set of 2709 Mor-regulated genes was determined. GO enrichment analysis of the regulated genes by Xoo or Mor suggested mitochondrion may be an arena for the up-regulated genes and chloroplast be another for the down-regulated genes by Xoo or Mor. Cytokinin-related processes were most frequently repressed by Xoo, while processes relevant to jasmonic acid and abscisic acid were most frequently activated by Xoo and Mor. Among genes responsive to Xoo and Mor, defense responses and diverse signaling pathways were the most frequently enriched resistance mechanisms. InterPro annotation showed the zinc finger domain family, WRKY proteins, and Myb domain proteins were the most significant transcription factors regulated by Xoo and Mor. KEGG analysis demonstrated pathways including ‘phenylpropanoid biosynthesis’, ‘biosynthesis of antibiotics’, ‘phenylalanine metabolism’, and ‘biosynthesis of secondary metabolites’ were most frequently triggered by Xoo and Mor, whereas ‘circadian rhythm-plant’ was the most frequent pathway repressed by Xoo and Mor. CONCLUSIONS: The genes identified here represent a robust set of genes responsive to the infections of Xoo and Mor, which provides an overview of transcriptional reprogramming during rice defense against Xoo and Mor infections. Our study would be helpful in understanding the mechanisms of rice disease resistance.